Results of a Qualitative Study to Develop a Patient Reported Outcome Measure for Patients with 4 Subtypes of Soft Tissue Sarcoma. (14th May 2017) - Skalicky, Anne M.; Ghate, Sameer R.; Perez, Jose Ricardo; Rentz, Anne M.
Abstract : Objective . The objective of this research was to develop a disease-specific symptom inventory for soft tissue sarcoma. Methods . Literature review and clinical expert and patient interviews were conducted to determine disease-specific symptoms important to patients with one of the four STS subtypes. Clinical experts identified the most relevant STS symptom items from the item pool developed from literature review. Concept elicitation interviews were conducted with patients to elicit their STS symptom experiences followed by a completion of the draft symptom list via web survey. A cognitive interview was conducted on the comprehension and importance of the symptom items. Results . Eighty-three symptom items were compiled and discussed with three clinical experts who identified 26 symptoms specific to the four STS subtypes. A total sample of 27 STS participants with self-reported leiomyosarcoma (74%), undifferentiated sarcoma (15%), synovial sarcoma (7%), or liposarcoma (4%) diagnosis completed the web survey and 10 were interviewed. The draft 12-item STS-specific symptom inventory includes abdominal pain, pressure in abdomen, early satiety, bloating, gastrointestinal pain, muscle pain, bone pain, heavy menstrual flow, shortness of breath, chest pain, cough, and painful menstruation. Conclusion . A number of symptoms are common across STS subtypes and may form a single STS symptom inventory.